The Implementation of the Restitution Triangle in Instilling Discipline of Congregational Obligatory Prayers at Pondok Pesantren Tahfidz Qur'an Lembah Serunting - Utama, Muhamad Risqi; Heriyah Oktaviani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research aims to improve the discipline of performing congregational obligatory prayers at the Tahfidz Qur’an Lembah Serunting Islamic Boarding School in Pagar Alam City using the Restitution Triangle Method approach. The Restitution Triangle is a method that leverages relationships between individuals, communities, and spiritual values to encourage behavioral change toward improvement. This approach integrates aspects of strengthening faith, social relationships, and consistency in fulfilling religious obligations. The research problem formulated in this study is how the Restitution Triangle method can be applied as an approach to instill discipline in students and whether this approach is effective in increasing the discipline of performing congregational obligatory prayers. The method used in this research is Classroom Action Research. with a qualitative descriptive approach, and data collection techniques include observation, interviews, and documentation. The results of this research indicate a convincing improvement through the use of the Restitution Triangle method from cycle to cycle. Before the intervention, the average discipline score was 63.53%, which then increased to 105.34% in Cycle I and further improved to 90.74% in Cycle II. This data suggests that with the Restitution Triangle approach, students' discipline in performing congregational prayers can be significantly enhanced. The conclusion of this research is that the Restitution Triangle method effectively improves students' discipline in performing obligatory congregational prayers.